2007
DOI: 10.1002/hed.20752
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated pleomorphic sarcoma of the parotid gland: A rare pediatric case

Abstract: The classification of MFH has been recently debated. Nevertheless, our case is the second report of pediatric MFH involving the parotid gland. Surgical resection is the preferred treatment, but combined chemoradiation may be necessary in the head and neck region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…Head and neck localizations are very rare, their prevalence is about 1:1 000 000 . UHPS usually develops in older patients with a peak incidence in the seventh decade, but have also been reported in children . A review of English language literature identified 24 published cases of primary locations of UHPS in the parotid gland (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Head and neck localizations are very rare, their prevalence is about 1:1 000 000 . UHPS usually develops in older patients with a peak incidence in the seventh decade, but have also been reported in children . A review of English language literature identified 24 published cases of primary locations of UHPS in the parotid gland (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…3 UHPS usually develops in older patients with a peak incidence in the seventh decade, but have also been reported in children. 9 A review of English language literature identified 24 published cases of primary locations of UHPS in the parotid gland (Table 1). UHPS is more frequent in adults and is very rare in early childhood 4 as found in the literature where only 2 of the 24 cases described occurred in childhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Впервые она описана O'Brien и Stout в 1964 году, а в 1980-х годах была признана одной из самых распространенных мягкотканных сарком у взрослых. У детей встречается редко -око-ло 2-6% всех СМТ [2][3][4][5][6].…”
unclassified
“…Неблагоприятные прогностические факторы этой опухоли -мужской пол, подростковый возраст, первичная локализация в костях, а также глубокая инвазия в ткани [2].…”
unclassified